2004
DOI: 10.1111/j.1601-5223.1996.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypic Variation of the Common Shrew (Sorex Avaneus) in European Russia: Preliminary Results

Abstract: Despite the fact that the common shrew occurs abundantly throughout European Russia, almost nothing is known about the karyotypic variation of the species in this important part of its geographic range. We present G‐band karyotypic data on seven samples from well separated sites. The race first described by ANISKIN and LUKIANOVA (1989) from one site near Moscow was confirmed. This ‘Moscow’ race (XX/XYIY1Y2af, bc, gm, hn, j/l, kr, no, pq, tu) has a very extensive distribution in European Russia (over a longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 9 publications
(9 reference statements)
1
4
0
1
Order By: Relevance
“…Recently there has been the opportunity to extend this research at Academgorodok, through an INTAS-funded project to characterise the karyotypic variation in S. araneus over its whole Asian distribution (also other parts of the Former Soviet Union: see ORLOV et al 1996). This study has already confirmed the continued existence of the karyotypic polymorphism described by K R A L and RADJABLI (1974) and has demonstrated the occurrence of new karyotypic races (POLYAKOV et al 1997a,b).…”
supporting
confidence: 59%
“…Recently there has been the opportunity to extend this research at Academgorodok, through an INTAS-funded project to characterise the karyotypic variation in S. araneus over its whole Asian distribution (also other parts of the Former Soviet Union: see ORLOV et al 1996). This study has already confirmed the continued existence of the karyotypic polymorphism described by K R A L and RADJABLI (1974) and has demonstrated the occurrence of new karyotypic races (POLYAKOV et al 1997a,b).…”
supporting
confidence: 59%
“…Additional information: Individuals from Kostroma (Unzha river) were previously described as the Moscow race (Orlov et al 1996).…”
Section: Additional Informationmentioning
confidence: 99%
“…Currently, no less than 72 chromosomal races are recognized in total ( White et al 2010 ). The number of Russian chromosomal races has already reached 25 ( Orlov et al 1996 , 2007 , Bulatova et al 2000 , Shchipanov et al 2009 , Pavlova 2010 ). Only four of these races are common for Russia and some neighboring areas.…”
Section: Introductionmentioning
confidence: 99%
“…Only four of these races are common for Russia and some neighboring areas. They include the following: 1) the Neroosa race which spreads over the southern regions of Russia and Ukraine; 2) the West Dvina race which can be found in Russia – Belarus neighboring regions; 3) the Goldap race which inhabits the Baltic coast area of Poland and Kaliningrad region of western Russia; 4) the Ilomantsi race which occurs in the bordering areas of north-western Russia (Karelia) and Finland ( Orlov et al 1996 , 2007 , Bulatova et al 2000 , Shchipanov et al 2009 , Borisov et al 2009a ). As anticipated, regular studies of distribution of different races resulted in discoveries of interracial zones of contact in Russia ( Shchipanov et al 2009 , Orlov et al 2012 , Pavlova 2013 , Shchipanov and Pavlova 2013 ) and neighboring territories ( Borisov et al 2010 , 2013 ).…”
Section: Introductionmentioning
confidence: 99%